2008
DOI: 10.1007/s12098-008-0021-x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in patients with atopic dermatitis

Abstract: These results confirmed that development of asthma in patients with AD is more than normal population and AD can be a significant predisposing factor to developing asthma but the causative factors are not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…They provide a plausible explanation of why a large number of AD patients develop asthma and other allergic disorders later in life [35],[36]. Because TSLP overproduction is triggered by skin-barrier defects and faithfully mirrors the severity of these defects [15], our data emphasize that an early and aggressive treatment of the underlying skin-barrier defects in AD-prone patients [10],[11] may be more beneficial in preventing asthma than treating the outbreaks of AD lesions [6].…”
Section: Discussionmentioning
confidence: 59%
“…They provide a plausible explanation of why a large number of AD patients develop asthma and other allergic disorders later in life [35],[36]. Because TSLP overproduction is triggered by skin-barrier defects and faithfully mirrors the severity of these defects [15], our data emphasize that an early and aggressive treatment of the underlying skin-barrier defects in AD-prone patients [10],[11] may be more beneficial in preventing asthma than treating the outbreaks of AD lesions [6].…”
Section: Discussionmentioning
confidence: 59%
“…47 A positive SPT and high IgE levels (0.35 kU/l) have correlated with atopic and allergic disease, and systematic sensitization within 2-3 years after birth has been associated with allergic disease morbidity. 48 Probiotic interventions can reduce the incidence of eczema to a certain extent, but they cannot change the host allergic status.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma, rhinitis and eczema are the most common allergic diseases, among which atopic eczema has the highest incidence in infants and is the best predictor for subsequent allergic asthma and rhinitis in school-age children. 47 A positive SPT and high IgE levels (0.35 kU/l) have correlated with atopic and allergic disease, and systematic sensitization within 2-3 years after birth has been associated with allergic disease morbidity. 48 Probiotic interventions can reduce the incidence of eczema to a certain extent, but they cannot change the host allergic status.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the development of asthma in AD patients is more common, although the exact causative factors are not yet clear. In a study conducted by Pourpak et al [ 12 ] the prevalence of asthma in patients with AD was 27,5%.…”
Section: Atopic Marchmentioning
confidence: 99%